Manajemen Risiko Sistem Informasi Ujian Secara Daring Di Sekolah Tinggi Manajemen Asuransi Trisakti - Syahrial Sidik Syahrial Sidik; Wahyuari Wahyuari (Jurnal Green Growth dan Manajemen Lingkungan, 2023)
This study aims to determine the risk management of the Online Exam Information System at the Trisakti Insurance Management College (STMA Trisakti). This study uses primary data obtained from data sources, namely deputy chairman I, the head of the Company division, lecturers, and students, analyzed the risk management process sessions namely Communication and Consultation, Context Determination, Risk Assessment, Risk Treatment, monitoring, and review. The sampling technique used is non-probability sampling (purposive sampling) and risk will be analyzed using a probability impact matrix. Based on the results of the risk analysis of the Online Exam Information System, there are 3 risks in the medium category: Online exam information system according to online exam procedures, Manageable online exam risk management by KOMPTI, and High system maintenance.